Slovarska obravnava samostalnikov za poimenovanje oseb - Štumberger, Saška (Slavistična revija, 2019)
The article presents the dictionary treatment of nouns denoting persons in the Slovenian standard language. Names of persons and their dictionary treatment differ according to whether persons are named according to their biological or social functions and actions. Gender-neutral naming of persons, names meanings, and forms in gender-specific naming of female persons are presented based on materials in general interpretative dictionaries-in the two editions of the Slovar slovenskega knjižnega jezika (Dictionary of standard Slovenian language) and in the Slovar novejšega besedja slovenskega jezika (Dictionary of new Slovenian words).
Keywords: generical gender; generični spol; grammatical gender; lexicography; naming of persons; poimenovanje oseb; slovaropisje; Slovenian language; slovenščina; slovnični spol